Pengaruh Kualitas Sistem Dan Kualitas Informasi Terhadap Kepuasan Pengguna Enterprise Resource Planning-System Application And Product In Data Processing (ERP-SAP) Pada PT. Inalum (Persero) Sumatera Utara - Dessyana, Dessyana; Yolanda, Yola (Universitas Pendidikan Ganesha, 2022)
This study aims to test and analyze the impact of system quality and information quality on ERP-SAP user satisfaction in PT. Inalum (Persero) Sumatera Utara and to test and analyze whether service quality could moderate the relations between system quality and information quality of ERP-SAP user satisfaction in PT. Inalum (Persero) Sumatera Utara. Research is a quantitative study that uses primary data through the distribution of questionnaires. The population in this study were employees of PT. Inalum (Persero) Sumatera Utara which was authorized to use ERP-SAP. The study sample consisted of 161 employees. The data analysis used by researchers is SPSS. The results indicate that, simultaneously system quality and information quality had effect on ERP-SAP user satisfaction. Partially, only system quality had effect on ERP-SAP user satisfaction. The service quality did not moderate relations between system quality and information quality on ERP-SAP user satisfaction in PT. Inalum (Persero) Sumatera Utara..Â